Qualitative coronary artery calcium assessment on CT lung screening exam helps predict first cardiac events - Malcolm, Katherine B. (J Thorac Dis, 2018)
RESULTS: A total of 1,513 individuals underwent CTLS. Downstream data, pre-test cardiac risk factors and CAC scores were available for 88.3% (1,336/1,513). The average length of follow-up was 2.64 (SD ±0.72) years. There were a total of 43 events, occurring in 1.55% (6/386) of patients with mild CAC, 3.24% (11/339) of patients with moderate CAC, and 8.90% (26/292) of patients with marked CAC. There were no events among patients with no reported CAC (0/319). Using multivariable logistic modeling, the increased odds of an initial cardiac event was 2.56 (95% CI, 1.76–3.92, P<0.001) for mild CAC, 6.57 (95% CI, 3.10–15.4, P<0.001) for moderate CAC, and 16.8 (95% CI, 5.46–60.3, P<0.001) for marked CAC, as compared to individuals with no CAC. Time to event analysis showed distinct differences among the four CAC categories (P<0.001). CONCLUSIONS: Qualitative coronary artery calcification scoring of CTLS exams may provide a novel method to help select individuals at elevated risk for an initial cardiac event.